Using Pay for Performance to Improve Treatment Implementation for Adolescent Substance Use Disorders: Results From a Cluster Randomized Trial - Garner, Bryan R. (Arch Pediatr Adolesc Med, 2012)
OBJECTIVE: To test whether pay for performance (P4P) is an effective method to improve adolescent substance use disorder treatment implementation and efficacy. DESIGN: Cluster randomized trial. SETTING: Community-based treatment organizations. PARTICIPANTS: Twenty-nine community-based treatment organizations, 105 therapists, and 986 adolescent patients (953 with complete data). INTERVENTION: Community-based treatment organizations were assigned to 1 of the following conditions: the implementation-as-usual (IAU) control condition or the P4P experimental condition. In addition to delivering the same evidence-based treatment (ie, using the Adolescent Community Reinforcement Approach [A-CRA]), each organization received standardized levels of funding, training, and coaching from the treatment developers. Therapists in the P4P condition received US $50 for each month that they demonstrated competence in treatment delivery (ie, A-CRA competence) and US $200 for each patient who received a specified number of treatment procedures and sessions (ie, target A-CRA) that has been found to be associated with significantly improved patient outcomes. MAIN OUTCOME MEASURES: Outcomes included A-CRA competence (ie, a therapist-level implementation measure), target A-CRA (ie, a patient-level implementation measure), and remission status (ie, a patient-level treatment effectiveness measure). RESULTS: Relative to therapists in the IAU control condition, therapists in the P4P condition were significantly more likely to demonstrate A-CRA competence (24.0% vs 8.9%; event rate ratio, 2.24; 95% CI, 1.12-4.48; P=.02). Relative to patients in the IAU control condition, patients in the P4P condition were significantly more likely to receive target A-CRA (17.3% vs 2.5%; odds ratio, 5.19; 95% CI, 1.53-17.62; P=.01). However, no significant differences were found between conditions with regard to patients' end-of-treatment remission status. CONCLUSION: Pay for performance can be an effective method of improving treatment implementation. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT01016704